Childhood Sexual Trauma: Impacts and Counselor Competencies - Tadros, Eman; Wunderlich, Shawn (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: The Rape, Abuse, & Incest National Network (RAINN) reports one in nine girls and one in 53 boys under 18 experience childhood sexual abuse. This review explores literature on childhood sexual abuse in the U.S., focusing on intrafamilial abuse and its impact on mental health, emphasizing the role of counselors.Methods and Materials: A systematic review of relevant studies on childhood sexual abuse, risk factors, effects, therapy perceptions, and the common factors model was conducted, with a specific focus on intrafamilial abuse.Findings: Risk factors, such as family dynamics, contribute to intrafamilial abuse, which results in long-lasting psychological effects like PTSD, depression, and anxiety. Survivors' perceptions of therapy vary, but effective treatment often involves strong therapeutic relationships. The common factors model emphasizes empathy and client-centered approaches in therapy.Conclusion: Intrafamilial abuse requires specialized therapeutic interventions. Further research on the treatment of adult female survivors is necessary to improve therapeutic outcomes.